The Globalisation of Crime : Understanding Transitional Relationships in Context. - Findlay, Mark (Cambridge University Press, 2003)
Crime is becoming as much a feature of the emergent globalized culture as other forms of consumerism. The Globalization of Crime presents an integrated theory of crime and social context and is the first book to challenge existing analyses of crime in the context of globalization.